Analysis of the Effectiveness of Medical Waste Management Policies at Health Laboratory - Andri Yanti; Subang Aini Nasution; Hartono Hartono; Rapael Ginting; Sondang Selviana Silitonga; Ismail Usman (Indonesian Journal of Global Health Research, 2026)
The implementation of medical waste management policies at the laboratory level still faces challenges in the form of non-compliance with operational standards, limited resources, and weak evaluative monitoring. This study aims to analyze the effectiveness of medical waste management policies at the UPTD Puskesmas in Jambi City. This study uses a case study method, with a qualitative approach, where the sampling technique used is purposive sampling. Total number of informants in this study is 20 people. Data obtained from interviews, observations, and document analysis will be analyzed thematically to identify emerging patterns, themes, and issues related to medical waste management policies. As a result of data management, there are several regulations for medical waste management at the UPTD Puskesmas in Jambi City, starting from the Law on Environmental Protection and Management, Presidential Regulations, Ministerial Regulations, and SOPs for the Puskesmas themselves. Medical waste management is carried out through several stages, starting from sorting, internal transportation, temporary storage, to external transportation and processing involving third parties. There are challenges faced in medical waste management, including untrained human resources, budget constraints, and inconsistent external transportation schedules. Based on the results of the analysis and discussion regarding the effectiveness of medical waste management policies at the UPTD Labkesda Jambi City, it can be concluded that the Regulatory and Implementation Aspects of the UPTD Labkesda Jambi City already have a strong regulatory basis, both externally and internally and Cooperation Agreements with third parties. However, there is still a gap between written policies and implementation in the field, so that the effectiveness of the policy has not reached its optimal point. The Human Resources Aspect shows that the quality and quantity of human resources are the main determinants in waste management. The Infrastructure Aspect shows that the facilities are quite adequate, but more modern and sustainable waste management is needed.